A Practical Approach to the Time Complexity of Algorithms - Hynek, Josef (Proceedings of the International Conference on European Association for Education in Electrical and Information Engineering, 2019)
Rapid development of information technology brings along the constant need for inclusion of new and attractive modules into ICT specialist curricula and there quite common attempts to reduce less attractive parts of ICT curricula and, unfortunately, theoretical subjects are very often among the candidates for possible cuts or even replacements by something more applicable. We believe that the theoretical foundations of computer science are very important and that there is a possibility to persuade our students that they must be aware of the theoretical principles in order to become a real specialist in this field. This paper describes our approach taken to teaching the module of algorithms complexity with a special focus on the types of practical examples utilized to demonstrate the usefulness and applicability of the theory of algorithms complexity.